Experimental study on the dual-gas co-production from hydrate deposit and its underlying gas reservoir. (1st November 2022) - Li, Rui; Cao, Bo-Jian; Chen, Hong-Nan; Wang, Xiao-Hui; Sun, Yi-Fei; Sun, Chang-Yu; Liu, Bei; Pang, Wei-Xin; Li, Qing-Ping; Chen, Guang-Jin
Abstract: Short gas production periods and high production costs are two main challenges for the commercial exploitation of natural gas hydrates (NGHs). The NGHs deposit with enriched underlying free gas has drawn more attention, because the dual-gas co-production from hydrate zone and underlying free gas zone are expected to increase gas yields. We designed a method to prepare this kind of hydrate deposits that a hydrate layer over a free gas layer, and performed a series of dual-gas co-exploitation experiments to investigate its gas production characteristics via depressurization method. Results demonstrate that the temperature of hydrate layer and free gas layer exhibit different variation tendency during gas production process and lower production pressure attributes to higher gas production rate and gas recovery ratio. The wellbore set at underlying free gas layer is recommended because it can avoid lower initial local permeability around the well and prevent ice plug or hydrate reformation during gas production process. Meanwhile, it enhances the movement of hydrate decomposition front and further improves gas production efficiency. Compared with the NGHs reservoir with a single hydrate zone, the dual-gas co-production has higher gas production efficiency and lower temperature decrease to maintain the driving force of hydrate dissociation. Graphical abstract: The dual-gas co-production with the wellbore set at underlying free gas layer can avoid lower initial local permeability around the well, prevent ice plug or hydrate reformation during gas production process, and enhance the movement of hydrate decomposition front. Image 1 Highlights: Dual-gas co-production from hydrate zone and underlying free gas zone was investigated. Temperature tendency is different for hydrate and free gas layers during production. Lower production pressure attributes to higher gas production rate and gas recover ratio. The wellhead at underlying free gas layer avoids sharply temperature decrease of hydrate layer. Dual-gas co-production has higher gas production efficiency and lower temperature decrease.